جماليات المطلع وحسن الاستهلال في ديوان الإسلام "لابن الخلوف القسنطيني" - نجاحي، نجلاء; زيتوني، فائزة (جامعة قاصدي مرباح - ورقلة, 2021)
إن اهتمام الشعراء الأوائل بمطالع قصائدهم دليل على دورها الفعال في التأثير في النفوس، إذ يعد حسن الاستهلال مؤشرا على البراعة والحذق وإجادة صنعة النظم، فهو الوسيلة المثلى للولوج إلى رحاب القصيدة، والشاعر المجيد يتمكن من صياغة بدايات قصائده صياغة لائقة مبهرة، بما يجذب النفوس لتكون كل كلمة ضمنه لها من الخصائص والسحر ما يعلق في الأسماع. ومن الثابت أن كل مطلع محاط ببواعث نفسية وشعورية، إلى جانب بواعث أدبية وبلاغية يقصدها الشاعر ليؤدي دوره الجمالي والنفسي في المتلقين، ومن الشعراء الذين نوعوا وأجادوا افتتاح قصائدهم ابن الخلوف القسنطيني في ديوان الإسلام.
The interest of early poets in reading their poems is evidence of their effective role in influencing souls, as good initiation is an ind of systems-making, as it is the best way to access the poem's space, and the glorified ication of dexterity, cleverness and mastery poet is able to formulate the beginnings of poems in a decent and tight formulation, by attracting souls So that every word in it has its own characteristics and magic that hangs in the ears. It is well established that every scholar is surrounded by psychological and emotional motives, as well as literary and rhetorical motives intended by the poet to play his aesthetic and psychological role in the recipients, and among the poets who diversified and excelled in the opening of their poems, Ibn al-Khalouf al- Constantini, in famous poem, "Diwan al-Islam."
Keywords: الأدب الإسلامي -- الشعر الإسلامي -- النقد الأدبي -- شعر المدح -- مدح النبي